Sessile serrated adenomas: high-risk lesions? - Salaria, Safia N. (2012)
Sessile serrated adenomas (SSAs) were unrecognized in pathology and gastroenterology practice until about 2005; we have diagnosed them since 2001, allowing up to 10 years of follow-up. We evaluated follow-up of patients with sessile serrated adenoma diagnosed between 2002 and 2004 in our teaching institution and compared it to follow-up of randomly selected tubular adenomas. Materials from patients diagnosed with sessile serrated adenoma from January 2002 to December 2004 were reviewed. A control group of patients with sporadic tubular adenomas was selected. Ninety-nine sessile serrated adenomas from 93 patients were diagnosed between January 2002 and December 2004. Forty three patients (46.2%) had follow-up colonoscopy. One or more lesions were found in 42 (97.6%) of 43 patients. Mucinous adenocarcinoma was diagnosed in 1 (2.3%) of 43 patients, and 1 (2.3%) of 43 patients had high-grade dysplasia in an sessile serrated adenoma. Sessile serrated adenomas were found in 22 (51.2%) of 43 patients, 16 (37.2%) of 43 patients had tubular adenomas, and hyperplastic polyps were diagnosed in 18 (41.9%) of 43. Ninety-two patients with tubular adenomas between January 2002 and December 2004 formed the control group. Sixty-six patients (71.7%) received follow-up colonoscopy. Most (53/66, 80.3%) patients had tubular adenomas on follow-up, 12 (18.2%) of 66 patients had hyperplastic polyps, and 2 (3.0%) of 66 patients had a sessile serrated adenoma. The follow-up of sessile serrated adenomas from the study period (2002 to 2004) was more rigorous than proposed for sporadic tubular adenomas (patients with sporadic tubular adenomas were also followed up more aggressively than suggested by guidelines). Those with follow-up were managed as per advanced adenomas; their clinical outcomes supported this. These results suggest that guidelines for following up patients with sessile serrated adenomas as per advanced adenomas are warranted.